2017
DOI: 10.21037/jtd.2017.04.23
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of minimally invasive esophagectomy in a tertiary referral center for esophageal cancer

Abstract: years, high morbidity rates are still recorded (5,6). In an effort to reduce the postoperative morbidity associated with open esophagectomy various minimally invasive esophagectomy (MIE) techniques have been introduced and developed during the recent years. MIE is believed to minimize the surgical trauma and subsequently the postoperative pain resulting in a faster mobilization and recovery with reduced postoperative complication rates and shorter hospital stay compared to the open procedure. During the last 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 23 publications
1
16
1
Order By: Relevance
“…Reports propose the learning curve of MIE to be around 30–40 operations (15, 16) to overcome the technical difficulties and even suggested as high as 119 surgeries to surpass the learning curve regarding anastomotic insufficiency (17). The present study of 51 MIE patients operated in a medium volume center proposes similar results to Nilsson et al reporting on the successful implementation of MIE at a Swedish high-volume center in 173 patients over 5 years (18). In the present study, the duration of surgery was unaffected by the transition to MIE, possibly reflecting the present surgeons’ extensive experience in other advanced laparoscopic procedures.…”
Section: Discussionsupporting
confidence: 91%
“…Reports propose the learning curve of MIE to be around 30–40 operations (15, 16) to overcome the technical difficulties and even suggested as high as 119 surgeries to surpass the learning curve regarding anastomotic insufficiency (17). The present study of 51 MIE patients operated in a medium volume center proposes similar results to Nilsson et al reporting on the successful implementation of MIE at a Swedish high-volume center in 173 patients over 5 years (18). In the present study, the duration of surgery was unaffected by the transition to MIE, possibly reflecting the present surgeons’ extensive experience in other advanced laparoscopic procedures.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have shown higher postoperative mortality associated with neck anastomosis (25,27). Also, part of the benchmark centers, as addressed by the authors, were still in the middle of their learning curve, and also changing the approach used during the study period (28). The results can be further improved with omental reinforcement flaps, also used routinely at our center, which were shown to decrease overall leak rates (29).…”
Section: Discussionmentioning
confidence: 89%
“…This indicates that, Ivor-Lewis surgery has higher safety. This may be because the living quality of patients in this group is higher after the operation [6][7][8][9] . Clinical literatures and reports indicate that, Ivor-Lewis surgery is relatively simple during the treatment of middle-lower section esophageal cancer, while McKeown surgery is relatively complex and increases the risk of recurrent laryngeal nerve injury, thus reducing patients' living quality.…”
Section: Discussionmentioning
confidence: 99%